Speed Control Using an Integral Sliding Mode Controller for a Three-Phase Induction Motor - Samar Abdulkareem AL-Hashemi; Ayad AL-Dujaili; Ahmed R. Ajel (Journal of Techniques)
Induction motors are widely used in commercial and industrial applications due to their robustness, high efficiency, low maintenance requirements and durability among other reasons. Consequently, their speed should be controlled for better performance. This paper describes utilization of a scalar speed control of a three-phase squirrel cage induction motor (SCIM) to control a motor’s speed using an integral sliding mode controller (ISMC). The controller was tested under various operating conditions. The results are compared with a case employing a conventional PI controller. It was found that speed control by ISMC has a 0.16 RPM steady-state error, 0.03 s to reach steady-state from a standstill, and a 5% overshoot. All of these are lower values as compared to the results of a conventional PI controller. In this paper, the robustness of each controller to uncertainties is checked. Simulation results show the advantages of ISMC control methods. The system is simulated using MATLAB SIMULINK R2017a.